Advanced simulation techniques for the transport of routine atmospheric discharges using the JRODOS system. (March 2023) - Selivanova, Anna; Hůlka, Jiří; Kotík, Lukáš; Kuča, Petr; Rubovič, Peter; Malátová, Irena; Helebrant, Jan; Koc, Josef; Rulík, Petr; Vlček, Ondřej
Abstract: This work is dedicated to a study of routine atmospheric discharges from the Dukovany Nuclear Power Plant (NPP), Czechia. Radionuclide discharges and their transport in the environment were simulated using the JRODOS system. JRODOS was originally designed to forecast the atmospheric transport of radionuclide releases. However, the potential of JRODOS can be widened with the use of external scripts. Routine discharges can be simulated as 1-h immediately following discharges when they are summed and rescaled in accordance with the actual discharged activities. For calculations of routine discharges, we selected artificial radionuclides measured in the spectra of aerosol filters originating from the vicinity of the Czech NPPs. According to the simulated map of volumetric activities integrated over a longer period, new aerosol sampling sites can be proposed in the surroundings of the NPP of interest. The simulations have also been compared with the detection levels of selected radionuclides detected on aerosol filters. Highlights: A methodology for simulating routine discharges using JRODOS has been proposed. JRODOS has been automated, with the use of scripts and third-party components. A map of volumetric activities after routine discharges has been obtained. Simulations have been compared with detection levels for aerosol filters.